An Fundamental Current Reference Control Strategy for DSTATCOM under Various Load Situations - Sri Prakash CH (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Effort for power quality enhancement is gradually raised in power transmission and distribution system. In a distribution system, it is a pre-requisite consumer related concern which is addressed by evading the mis-operation of massive power electronic load apparatus. Due to this, voltage/current harmonic distortions are acquired at common coupling point, which influences the disruption of quality power in a distribution system. A reliable and efficient active power conditioner is utilized for acquiring the power quality features in a three phase distribution system with attractive control objective. Over the classical conditioning techniques, a D-STATCOM plays a key role in a distribution system for power quality enhancement. Formal control objectives are adversed with incredible switching losses due to extreme harmonized frequencies in a reference current component. This paper proposes the imperative reference current extraction scheme for optimal functioning of DSTATCOM with reduced switching losses and gaining the incredible efficiency. The validation of DSTATCOM with proposed control strategy under several load situations (linear/non-linear & balanced/un-balanced) is evaluated by using Matlab/Simulink platform and simulation results are conferred.